Systemic treatment with interferones in oncology - Reberšek, Martina (Onkologija : Slovenian Journal of Oncology, 2017)
Interferons are an integral part of communication between the cells responsible for triggering the protective defenses of our immune system. In oncology, they are administered in prescribed doses to treat different cancers. They are of utmost importance in adjuvant treatment of malignant melanoma, namely in high doses of interferon α2b. Malignant melanoma is a highly aggressive malignant disease that is curable in more than 80 % of patients, if surgically removed in early stages of the disease. If, upon detection, regional lymph nodes are already positive, an incurable metastatic disease develops in more than 50 % of patients. For patients with a greater possibility of disease recurrence (stages IIB, IIC, and III), adjuvant therapy with a high dose of interferon α2b is recommended in Europe; while for high-risk stage IIIA (node metastasis > 1 mm) and stages IIIB and IIIC, a high dose of the anti-CTLA monoclonal antibody ipilimumab is recommended in the United States. The side effects of a high dose of interferon are manageable with a well-educated and compliant patient.